DAYA HAMBAT GEL PROPOLIS DARI SULAWESI SELATAN TERHADAP PERTUMBUHAN BAKTERI PORPHYROMONAS GINGIVALIS - Asdar Gani; Hetty Noveiliga Cindrakori (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2015)
Background : Periodontal disease is caused by various factors.Bacterial deposit plays an important role against the occurrence of periodontal disease. One of the bacterias that contribute to the occurrence of periodontal disease is Porphyromonas gingivalis. Propolis is a natural substance contains antibacterial properties which are different depends on the type of propolis. Propolis has been used for the treatment of apthous ulcer, candidiasis, gingivitis, periodontitis, and pulpitis. Purpose : The purpose of the study is determine propolis gel Trigona sp inhibitionfrom South Sulawesi on the growth of Porphyromonas gingivalis. Methods : This research is an experimental laboratories. Inhibition test performed a diffusion method using propolis and metronidazole gel.Inhibition zone of propolis and metronidazole gel against Porphyromonas gingivalis were measured using calipers after incubation 1x24 hours, 2x24 hours, and 3x24 hours. Result :The zone of propolis gel and metronidazole gel inhibition against Porphyromonas gingivalis observed in1x24 hours, 2x24 hours, 3x24 hours.Propolis gel consecutive are6.17±0.48 mm, 5.76±0.55 mm, 5.23±0.32 mm, whereas metronidazole gelconsecutive are 13.68 ± 1.66, 13.94 ± 2:03, 12.90 ± 1.96 mm, and the difference of both inhibition zone based on time 1x24 hours, 2x24 hours, 3x24 hours are7.51, 8.18, 7.66 mm. Conclusion: South Sulawesi propolis gel have inhibitory effect on the growth of P. gingivalis bacteria. While the inhibition zone of South Sulawesi propolis gel is smaller than Metronidazole gel.